2018
DOI: 10.1088/1475-7516/2018/05/049
|View full text |Cite
|
Sign up to set email alerts
|

Quantum standard clocks in the primordial trispectrum

Abstract: We calculate the primordial trispectrum of curvature perturbation in quasi-single field inflation, with general sound speeds for both the inflaton and the massive scalar. Special attention is paid to various soft limits of the trispectrum, where the shape function shows characteristic oscillatory pattern (known as the quantum primordial standard clock signal) as a function of the momentum ratio. Our calculation is greatly simplified by using the "mixed propagator" developed under a diagrammatic representation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…In this section following the method introduced in [75,76] for quasi-single-field inflation, but, regarding the QSMF inflationary regime we want to review briefly the S-K formalism and propagators. The diagrammatic approach based on in-in formalism is reviewed in [75,76] as well.…”
Section: Diagrammatic Rules and Mixed Propagatormentioning
confidence: 99%
See 4 more Smart Citations
“…In this section following the method introduced in [75,76] for quasi-single-field inflation, but, regarding the QSMF inflationary regime we want to review briefly the S-K formalism and propagators. The diagrammatic approach based on in-in formalism is reviewed in [75,76] as well.…”
Section: Diagrammatic Rules and Mixed Propagatormentioning
confidence: 99%
“…In this section following the method introduced in [75,76] for quasi-single-field inflation, but, regarding the QSMF inflationary regime we want to review briefly the S-K formalism and propagators. The diagrammatic approach based on in-in formalism is reviewed in [75,76] as well. Additionally, it can be showed that the diagrammatic method presented in [75,76] is very close to the usual Feynman rules in diagrammatic method, except that the space and the time are treated the same, and that here the model contains two types of propagators introduced by either + or −.…”
Section: Diagrammatic Rules and Mixed Propagatormentioning
confidence: 99%
See 3 more Smart Citations